What do my students need? Deep analysis of student's individual cognitive ability using person diagnostic map - Moh. Irma Sukarelawan; Toni Kus Indratno; Widodo Widodo; Pratiwi Dwijananti; Fitri Nur Hikmah; Nurul Syafiqah Yap Abdullah (Universitas PGRI Kanjuruhan Malang, 2024)
This research aims to evaluate students' conceptual understanding in the field of physics, focusing on the concepts of heat and temperature, using the Person Diagnostic Map (PKMAPs) approach. This method allows individual assessment of students' conceptual understanding, going beyond the limitations of conventional analysis methods that focus on groups. This research used a survey involving eight students from a private university in Yogyakarta, Indonesia. Data was collected through a multiple-choice test of 20 items, processed using Ms. Excel and Winsteps 4.6.1. The research results show that PKMAPs are effective in identifying individual student understanding, including detecting